(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Nutritional problems among adolescents remain a public health concern that requires serious attention, particularly those related to unbalanced dietary patterns and suboptimal healthy lifestyle behaviors. Adolescents are a vulnerable age group prone to both undernutrition and overnutrition, which may negatively affect health status and future productivity. Balanced nutrition education is a preventive strategy that can improve adolescents’ knowledge and awareness in preventing nutritional problems. This community service activity aimed to increase students’ knowledge of balanced nutrition as an effort to prevent nutritional problems at SMK Pembangunan Lubuk Pakam. The activity was conducted through nutrition education using interactive lectures, discussions, and simulations of the “My Plate” concept, involving 26 twelfth-grade students. Evaluation was carried out using pre-test and post-test methods to assess changes in students’ knowledge levels before and after the educational intervention. The results showed a significant improvement in students’ knowledge, indicated by an increase in the proportion of students with good knowledge from 23.1% to 69.2%, while the proportion of students with poor knowledge decreased from 38.5% to 3.9%. In addition, students demonstrated positive responses and high enthusiasm throughout the activity. Balanced nutrition education was proven to be effective in improving students’ understanding of balanced nutrition principles and the importance of healthy eating habits. This activity is expected to contribute to the prevention of nutritional problems among adolescents by enhancing knowledge, awareness, and motivation to adopt healthy lifestyle practices in daily life.